2007
DOI: 10.1002/ajmg.a.31983
|View full text |Cite
|
Sign up to set email alerts
|

Mandibuloacral dysplasia and a novel LMNA mutation in a woman with severe progressive skeletal changes

Abstract: A 56-year-old Japanese woman with mandibuloacral dysplasia and type A lipodystrophy is described. Mutation analysis identified a homozygous missense mutation (1585G > A) in exon 9 of the LMNA gene that replaces well-conserved residue alanine at position 529 to threonine (A529T). The woman showed, in addition to the usual clinical manifestations of the disorder, severe progressive skeletal changes: osteoporotic changes with multiple fractures; osteolysis of the right radius; and destructive changes of the verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 16 publications
3
23
0
1
Order By: Relevance
“…Similar phenotype combining mandibuloacral dysplasia (MAD), progeroid appearance, and rigid spine muscular dystrophy was caused by the p.R471C homozygous mutation in LMNA [Zirn et al, 2008]. A 56-year-old Japanese woman with MAD, type A lipodystrophy and severe progressive skeletal changes showed the homozygous p.A529T mutation [Kosho et al, 2007]. Cao and Hegele [2003] reported heterozygous mutations p.R527C/p.R471C in a female who initially was thought to have atypical HGPS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar phenotype combining mandibuloacral dysplasia (MAD), progeroid appearance, and rigid spine muscular dystrophy was caused by the p.R471C homozygous mutation in LMNA [Zirn et al, 2008]. A 56-year-old Japanese woman with MAD, type A lipodystrophy and severe progressive skeletal changes showed the homozygous p.A529T mutation [Kosho et al, 2007]. Cao and Hegele [2003] reported heterozygous mutations p.R527C/p.R471C in a female who initially was thought to have atypical HGPS.…”
Section: Discussionmentioning
confidence: 96%
“…MADA, as FPLD2, is caused by mutations in the LMNA gene (LMNA; OMIM# 150330) encoding the A and C lamins, intermediate filaments of the nuclear envelope. The most common MADA defect is a homozygous missense mutation (p.R527H) in the C-terminal domain of lamins A/C [Novelli et al, 2002;Shen et al, 2003], but different homozygous or compound heterozygous patients have been reported [Cao and Hegele, 2003;Plasilova et al, 2004;Garg et al, 2005;Kosho et al, 2007;Lombardi et al, 2007;Agarwal et al, 2008;Zirn et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…They form a meshwork located between the inner nuclear membrane and the chromatin, so they play a fundamental role in the maintenance of the size and shape of the nucleus (7) and in several nuclear processes such as transcription, chromatin organization and DNA replication. Mutations in the LMNA gene can bring about cardiac and skeletal muscle diseases, lipodystrophy and premature ageing phenotypes (8)(9)(10). Mandibuloacral dysplasia (MAD) is also due to a mutation in another gene (i.e.…”
mentioning
confidence: 99%
“…Second, similar but more extensive skeletal changes were recently described in a Japanese woman with the novel LMNA (A529T) homozygous mutation, who is in fact the oldest (56-year-old) MADA patient so far described [Kosho et al, 2007]. Third, analysis of MADA patients fibroblasts showed that the severity of both unprocessed prelamin A accumulation and chromatin disorganization was age related [Filesi et al, 2005].…”
mentioning
confidence: 55%
“…We describe elbow deformities in a previously characterized male 43-year-old patient, with homozygous LMNA missense mutation (R527H) [Novelli et al, 2002], who is the second oldest studied MADA patient [Kosho et al, 2007].…”
mentioning
confidence: 99%